Semi-empirical level ice resistance prediction methods. Issue 1 (2nd January 2017) - Erceg, Sandro; Ehlers, Sören
ABSTRACT: Ship performance in ice depends on numerous design aspects, such as ensuring adequate thrust, appropriate arrangement of the propellers, as well as a hull designed to reduce the resistance, in both ice and open water. All these efforts require ice resistance estimates. In early design stages, semi-empirical methods represent the most commonly used choice. However, being based on a limited amount of empirical data, these methods are expected to be restricted to ships of similar characteristics to the ones used in their development. This paper reviews six semi-empirical level ice resistance prediction methods, applied to four ships of different sizes and bow shapes. The results are presented along with the available full-scale resistance measurements. It is found that their deviation from the measurements varies substantially with the ship size. The methods show significant discrepancies, with the deviations from one another as large as 100–200%, especially for larger ships.